2021
DOI: 10.3346/jkms.2021.36.e227
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric and Parents' Attitudes Towards COVID-19 Vaccines and Intention to Vaccinate for Children

Abstract: Background Coronavirus disease 2019 (COVID-19) vaccination is necessary to reach herd immunity and essential for mitigating the spread of the pandemic. In May 2021, the US FDA and the EU have expanded the emergency use authorization for a COVID-19 vaccine to children aged 12 to 15. The aim of this study was to investigate parental acceptability of COVID-19 vaccination for their children, factors affecting their acceptability, and children's perceptions of COVID-19 vaccines in Republic of Korea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
71
4
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 16 publications
(16 reference statements)
11
71
4
4
Order By: Relevance
“…In October 2021, 2 weeks prior to the anticipated FDA approval for COVID-19 vaccination of children between the ages of 5 and 11 years, only 41% of a racially and ethnically diverse national sample of female guardians planned to have their young children vaccinated, 25% were unsure, and 34% were unwilling. This percentage is consistent with most prior reports of COVID-19 vaccination rates for children 12-17 years of age and anticipated rates for the emergency use approval for children 5-11 years of age [6][7][8][9][10][11][12][13][14][15]. However, rates significantly differed across racial/ethnic groups with 62% of non-Hispanic Asian parents compared to 31% non-Hispanic Black, 45% Hispanic, and 25% non-Hispanic White planning to vaccinate their child following FDA approval.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In October 2021, 2 weeks prior to the anticipated FDA approval for COVID-19 vaccination of children between the ages of 5 and 11 years, only 41% of a racially and ethnically diverse national sample of female guardians planned to have their young children vaccinated, 25% were unsure, and 34% were unwilling. This percentage is consistent with most prior reports of COVID-19 vaccination rates for children 12-17 years of age and anticipated rates for the emergency use approval for children 5-11 years of age [6][7][8][9][10][11][12][13][14][15]. However, rates significantly differed across racial/ethnic groups with 62% of non-Hispanic Asian parents compared to 31% non-Hispanic Black, 45% Hispanic, and 25% non-Hispanic White planning to vaccinate their child following FDA approval.…”
Section: Discussionsupporting
confidence: 86%
“…Since the vaccine was approved for children 12-17 years of age, US vaccination rates for this age group have been reported at 42% for the first dose and 32% for series completion [6]. Emerging data on parental intentions to have their 5-11-year-old children vaccinated for COVID-19 following FDA approval have reported similar rates ranging from 44% to 63% in the U.S. [7][8][9][10] and these are consistent with data from across the globe [11][12][13][14][15]. These percentages are troubling since population modeling indicates that vaccinating adolescents and children could reduce overall COVID-related mortality and case load [16].…”
Section: Introductionsupporting
confidence: 70%
“…We would expect that given guardians who completed surveys had children with more severe illness, families would be more willing to accept a vaccine, however, our findings are congruent with the CDC’s recent report of 48% of 16–17 year-olds and 39% of 12–15 year-olds who are fully vaccinated in the US as of 8 September 2021 [ 19 , 20 ]. In a recent study conducted in South Korea, guardians had a higher reported intent to vaccinate their child at 64.2%, mirroring their confidence in the effectiveness of COVID-19 vaccines of 64.8% [ 21 ]. In our study, adding a positive efficacy fact to the question in the second survey, appeared to influence guardians’ intent to vaccinate their child.…”
Section: Discussionmentioning
confidence: 99%
“…June 2021 among parents/guardians in South Korea and involving 226 participants reported an overall COVID-19 vaccine acceptance rate of 76.5% 79. An earlier global study by de Figueiredo and Larson, that was conducted during October-December 2020 involved 1103 participants from the country has shown an acceptance rate of 86.6% for COVID-19 vaccination.80 https://doi.org/10.2147/JMDH.S347669 DovePress Journal of Multidisciplinary Healthcare 2022:15 28 Sallam et al Dovepress Powered by TCPDF (www.tcpdf.org) Powered by TCPDF (www.tcpdf.org)…”
mentioning
confidence: 99%